Before Grenfell Fire, Safety and Deregulation in Twentieth-Century Britain - Ewen, Shane (IHR Shorts, 2023)
On 14 June 2017, flames engulfed a residential block of flats in West London. 72 people lost their lives and many hundreds more were traumatised as a national 'cladding crisis' unfolded. Yet the Grenfell Tower fire was a disaster foretold - the culmination of successive decades of deregulation, corporate greed and institutional failure to learn from the lessons of past multiple-fatality fires. By advocating a historical approach spanning the twentieth century, Before Grenfell deepens our contemporary understanding of the events surrounding the disaster and reveals how past decisions taken by governments and industry bodies created the conditions under which the fire occurred. Drawing upon unexplored archives as well as extensive use of published records, Shane Ewen's book traces the underlying causes of the fire through more than four decades of deregulation of fire precautions, scientific governance and building regulations by successive governments in thrall to the ideology of neoliberalism. In drawing upon several previous, and often forgotten, multiple-fatality fires, the book sheds light on the historic failures of policymakers to heed the lessons of the past in protecting vulnerable communities, arguing that good policymaking necessitates learning with history as well as learning from history.